2017
DOI: 10.1177/0954407017695141
|View full text |Cite
|
Sign up to set email alerts
|

Surface contamination of cars: A review

Abstract: This review surveys the problem of surface contamination of cars, which poses a growing engineering challenge to vehicle manufacturers, operators and users. Both the vision of drivers and the visibility of vehicles need to be maintained under a wide range of environmental conditions. This requires managing the flow of surface water on windscreens and side glazing. The rate of deposition of solid contaminants on glazing, lights, licence plates and external mirrors also needs to be minimised. Maintaining vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 57 publications
(93 reference statements)
0
24
0
1
Order By: Relevance
“…Instead of manipulating the velocity-time profile itself, one can also variate the rolling resistance coefficient C rr and the drag coefficient C d , which are used to compute M m (t) from v(t) (scenario C). In this way, uncertain weather and road conditions can be simulated, as C rr can increase by a factor up to δ rr = 1.3 on a wet road [12], and C d by a factor up to δ d = 1.2 due to rain drops contaminating the vehicle surface [13]. It is assumed that these mechanical coefficients are uniformly distributed, C rr (θ) ∈ U (C rr,dry , δ rr C rr,dry ) ,…”
Section: Driving Cyclementioning
confidence: 99%
“…Instead of manipulating the velocity-time profile itself, one can also variate the rolling resistance coefficient C rr and the drag coefficient C d , which are used to compute M m (t) from v(t) (scenario C). In this way, uncertain weather and road conditions can be simulated, as C rr can increase by a factor up to δ rr = 1.3 on a wet road [12], and C d by a factor up to δ d = 1.2 due to rain drops contaminating the vehicle surface [13]. It is assumed that these mechanical coefficients are uniformly distributed, C rr (θ) ∈ U (C rr,dry , δ rr C rr,dry ) ,…”
Section: Driving Cyclementioning
confidence: 99%
“…Gaylard & Duncan [21] as well as Gaylard et al [22] describe in their work the significant level of contamination onto the side of a SUV and notchback car due the wheel wake flow. In experimental and numerical investigations it is shown that the side soiling is mainly caused by flow being driven out the wheel house.…”
Section: Introductionmentioning
confidence: 99%
“…Management of surface contamination is becoming an increasingly important research area and design criterion for all major vehicle manufacturers. Apart from aesthetic considerations, vehicle soiling can also affect customer satisfaction in instances when dirt gets transported to their hands and clothes upon the contact with the vehicle exterior [1]. Contamination of rear surfaces represents a particular inconvenience, as dirt accumulating on these surfaces can degrade visibility through the rear screen, reduce rear wiper life, deteriorate the performance by lighting and rear view camera systems, as well as reduce visibility of rear lamps to other road users.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly problematic for square backed vehicle types, such as hatchbacks, estates and Sports Utility Vehicles (SUV) because the blunt rear geometry of these vehicles causes the formation of strong large-scale recirculating vortices that draw spray towards the rear surfaces [4]. Unlike rain droplets, spray generated by wheels can contain a diverse range of solid contaminants, such as soil, salt, sand, components of fuels and oils, carbon from combustion sources, brake and tyre wear and tarmac [1]. These materials, especially salt used for de-icing of roads, in combination with water can corrode the metalwork [5].…”
Section: Introductionmentioning
confidence: 99%